السياسة الطاقوية في الجزائر: قراءة في المرتكزات والتحديات - بخوش سارة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
يعتبر موضوع سياسات الطاقة في الجزائر من المواضيع التي حازت على الكثير من الاهتمام في الآونة الأخيرة باعتبارها تحوز على كم معتبر من الثروات المتجددة وغير المتجددة، لذلك سعت الجزائر منذ الاستقلال الى تثمينها واستغلالها بطريقة أكثر نجاعة وهذا ما يعود بالإيجاب على مختلف القطاعات الأخرى، ومن هذا المنطلق تهدف الدراسة الى تسليط الضوء على أهم مضامين السياسة الطاقوية في الجزائر في ظل التطورات الراهنة مبرزين أهم التحديات التي يواجهها صانع القرار لتحقيق الأمن الطاقوي، ومن أهم النتائج التي توصلت اليها الدراسة أن النفط والغاز يشكلان اللبنة الأساسية في بناء السياسية الطاقوية الجزائرية التي تقوم على ثلاث مرتكزات أساسية متمثلة في أمن الطاقة، حماية البيئية، والمسؤولية الاجتماعية. Abstract: The subject of energy policies considered as one of the most interested issues in Algeria as it possesses great capacities of renewable and non-renewable energy, therefore it has worked since independence to value and use it in more efficient way, which is positive on all other sectors. From this perspective the study shed light on the most important strategies and projects of the energy policy in Algeria under the current developments, and highlighting the challenges that decision-makers face to achieve energy security, the main finding of the study confirmed that oil and gas are the basic building block of the Algerian energy policy, which is based on three basic pillars: energy security, environmental protection, and social responsibility.